Construction of a global sustainability index (GSI): An evaluation tool for public policies aimed at sustainable milk production in contemporary times - Aragão, José Lima de; Pfeifer, Luiz Francisco Machado; Borrero, Manuel Antonio Valdés (Seven Editora, 2023)
The article aims to show methodological criteria for the construction of the Global Sustainability Index (IGS) and its importance in the evaluation of public policies of sustainable milk production in contemporary times. The economic, social, environmental, institutional, and technological dimensions are taken into consideration to better assess the sustainable development of economically active activities. The survey took place in Rondônia with 400 dairy farmers, where the IGS of the activity that reached average sustainability was obtained, IGS = 0.42. The economic dimension presented an index of 0.52, being the most sustainable among the analyzed dimensions. Following the decreasing order, comes social and environmental, with average sustainability of 0,44 and 0,41, respectively, and, with low sustainability, was the technological dimension, which presented an index of 0,39, and the institutional with 0,32 decimal points of sustainability. This result indicates the need for political and technological efforts to improve the sector’s performance. DOI:https://doi.org/10.56238/devopinterscie-232